FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SELF CARE PADA ORANG DEWASA YANG MENGALAMI HIPERTENSI DI PUSKESMAS KENDAL 01 KABUPATEN KENDAL - Indra Guna Winata; Ahmad Asyrofi; Andriyani Mustika Nurwijayanti (Jurnal Manajemen Asuhan Keperawatan, 2018)
Hypertension becomes a silent killer because in some cases it does not show any symptoms on the sufferer. The purpose of this study was to determine factors related to self care in adults who experienced hypertension in Kendal 01 health center. This research used a descriptive correlative design with cross sectional study design. Sample in this research use accidental sampling technique counted 96 respondents. The statistical test in this study used Kendall Taub's test and Chi Square Test. The result of this research can be concluded that there is a strong positive relationship between functional status with self care (p value 0,0001) (r = 0,523), Family support with self care (p value 0.0001) (r count 0,411) , And Emotional Change with self care (p value 0.0001). Then suggested to health service can give information and do home care by way of visit to every patient of hypertension.